Neural regulation of ILC2s in allergic airway inflammation - Thomas, Christopher M.; Peebles, R. Stokes (Frontiers in Allergy, 2023)
The sympathetic nervous system (SNS) and parasympathetic nervous system (PNS) regulate the effector functions of group 2 innate lymphoid cells (ILC2s) through β2 adrenergic receptor (ADRB2) and nicotinic/muscarinic cholinergic receptor signaling, respectively. To further maintain the critical balance between host-protective and pathogenic type 2 inflammation in the lungs, neuropeptides neuromedin B (NMB) and neuromedin U (NMU) function to suppress or promote ILC2 responses in synergy with IL-33/IL-25, respectively. Additionally, the release of ATP into the extracellular environment in response to cell death caused by challenge to the airway epithelial barrier quickly becomes converted into adenosine, which helps keep the inflammatory response in check by suppressing ILC2 responses. Besides neurotransmitter and neuropeptides derived from other cells, ILC2s further regulate allergic airway inflammation through the production of acetylcholine (ACh) and calcitonin gene-related peptide (CGRP). In this article we review the neuromodulation of ILC2s through cholinergic and adrenergic signaling, neuropeptides, and adenosine and its role in allergic airway inflammation. Furthermore, we discuss the potential clinical utility of targeting these pathways for therapeutic goals and address directions for future research.